Comisión Nacional de Nombres Geográficos 2000. Diccionario Geográfico de Cuba. La Habana: Oficina Nacional de Hidrografía y Geodesia. = [National Commission of Geographical Names 2000. Geographical Dictionary of Cuba. Havana: National Office of Hydrography and Geodesy] - Allen Adianys Collazo (Uusfilologinen yhdistys, 2022)
Kirja-arvostelu